Corrosion resistance of aluminum alloy AA2024 with hard anodizing in sulfuric acid-free solution - Cabral Miramontes, José Ángel; Gaona Tiburcio, Citlalli; García Mata, Estefanía; Esneider Alcála, Miguel Ángel; Maldonado Bandala, Erick; Lara Banda, María del Refugio; Nieves Mendoza, Demetrio; Olguín Coca, Javier; Zambrano Robledo, Patricia del Carmen; López León, Luis Daimir; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2022)
In the aeronautical industry, Al-Cu alloys are used as a structural material in the manufacturing of commercial aircraft due to their high mechanical properties and low density. One of the main issues with these Al-Cu alloy systems is their low corrosion resistance in aggressive substances; as a result, Al-Cu alloys are electrochemically treated by anodizing processes to increase their corrosion resistance. Hard anodizing realized on AA2024 was performed in citric and sulfuric acid solutions for 60 min with constant stirring using current densities 3 and 4.5 A/dm2. After anodizing, a 60 min sealing procedure in water at 95 °C was performed. Scanning electron microscopy (SEM) and Vickers microhardness (HV) measurements were used to characterize the microstructure and mechanical properties of the hard anodizing material. Electrochemical corrosion was carried out using cyclic potentiodynamic polarization curves (CPP) and electrochemical impedance spectroscopy (EIS) in a 3.5 wt. % NaCl solution. The results indicate that the corrosion resistance of Al-Cu alloys in citric acid solutions with a current density 4.5 A/dm2 was the best, with corrosion current densities of 2 × 10−8 and 2 × 10−9 A/cm2. Citric acid-anodized samples had a higher corrosion resistance than un-anodized materials, making citric acid a viable alternative for fabricating hard-anodized Al-Cu alloys.